Predicting Shisha Smoking Behaviour Among University Students In Nigeria: Moderating Roles Of Media Normalisation And Denormalisation - Oluwafunmilayo, Adu Agatha (2023)
The study elucidates the moderating roles of normalisation of shisha through social media and denormalisation of shisha through mainstream media in terms of pro-smoking and anti-smoking shisha related messages respectively.